Adaptive user interface for universal remote controller. (1st January 2015) - FanJiang, Yong–Yi; Chueh, Ting–Fang
This paper proposes a context–aware plug and play universal remote controller. Users can control an appliance easily which is recognised by NFC, download appliance's specific description through Bluetooth, and then generate dynamic graphical user control interface of the appliance. It depends on different contexts, including the permission level, personal style (colours, text, etc.), and location. The smart phone, which is getting more and more powerful, is always with us; online and personal. As a result, our system is made up with the extension of smart phone. We provide simple and intuitive graphic user interface, rather than the many buttons of the universal remote controller we have seen before.